Synthesis, Cellular Uptake and Biological Activity Against Pathogenic Microorganisms and Cancer Cells of Rhodium and Iridium N‐Heterocyclic Carbene Complexes Bearing Charged Substituents. Issue 32 (19th September 2013) - Simpson, Peter V.; Schmidt, Claudia; Ott, Ingo; Bruhn, Heike; Schatzschneider, Ulrich
Abstract: Four new N‐heterocyclic carbene (NHC) rhodium and iridium complexes decorated with anionic or cationic pendant groups to increase their water solubility and biological activity have been synthesised and characterised. The lipophilicity of the complexes was determined and the complexes that contained cationic phosphonium groups can be considered delocalised lipophilic cations (DLCs). All complexes were tested for their antibacterial, antiparasitic and anticancer activity, with only the phosphonium‐functionalised complexes showing moderate to high activity, whereas the exchange of metal from rhodium to iridium had a negligible effect. Most promising was the activity on Trypanosoma brucei, with IC50 values in the range of 150–400 nM and a selectivity index (SI) of up to 50. General toxicity on mammalian cell lines was a general problem, though, and needs to be mitigated in future work. Cellular uptake studies clearly confirmed that the cationic phosphonium groups facilitated uptake, which was linked with higher biological activity. Abstract : Four N‐heterocyclic carbene (NHC) rhodium and iridium complexes decorated with anionic or cationic pendant groups have been synthesised and characterised. Their antibacterial, antiparasitic, and anticancer bioactivity was studied on a number of organisms and cell lines.